O talento de gerir pessoas como chave da gestão de resíduos sólidos em espaços urbanos - Crosara, Regina (2014)
This research has as its central focus the analysis of the behavior of people on the implementation of Selective Collection Program in a building in the central area of Uberlândia / MG. Theories of Personnel Management and Human Motivation Theories were being applied and the change in behavior of residents was being investigated. The methodology consisted of literature research and participatory action research with meetings, interviews, and observations about the motivation of the residents. There was selective collection on site, with the program deployed 68% of the residents cooperated. The participation rate rose to 90% after a year and a half of the program. Biodegradable were destined for a recycling composting and 348kg experimental period, during the study period, were properly disposed, representing 30.8% of all waste generated. Visits resulted in 73 residential condominiums in Handbook of Practice. It is concluded that waste management depends on people management.